Responsivitas Pelayanan Publik (Studi Kasus Pelayanan Polres Rejang Lebong Terhadap Pengaduan Masyarakat) - Denyfita - Mochtar; Effed Darta Hadi; Syaiful Anwar AB (Student Journal of Business and Management, 2021)
The general research objective to be achieved from this study is to determine the responsiveness of the Rejang Lebong Resort Police service in handling public complaints on reports of complaints of violence against women and children. Research respondents are people who access complaint services or have reported to the Polres / Polsek in the Rejang Lebong Polres working area, which were taken by using the proportional random sampling technique of 20% of the 8 units of the Rejang Lebong Polres. The number of respondents taken was as many as 64 people. The results show 1) Respond to every community applicant who wants to get service This indicator includes good attitudes and communication from the service providers of the Rejang Lebong Police to the community. 2) Police officer/officers provide good communication to the community and are friendly so that the community feels comfortable. Officers/apparatus perform services quickly. This indicator is the readiness and sincerity of the police officer/apparatus in serving the community. The officers/apparatus who perform services quickly can be seen from their alertness. 3) Regarding the indicator of accuracy in serving. the timeliness of services provided by police officer/officers is still not in accordance with the wishes of the community. Due to several reasons, namely the existence of a system of discrimination by police officers/officers. This makes the community less responsive or unkind. 4) the timeliness of services provided by police officers/officers is still not in accordance with the wishes of the community. Because of several things, namely the existence of a system of discrimination carried out by police officers/officers. Based on this, the Accuracy Indicator of serving is focus, serious and thorough in providing services to the community both in work and in conversation. Regarding the indicators of accuracy in serving, Rejang Lebong Police have carried out their services carefully and in accordance with what is expected by the community as service recipients at the police station.Keywords: Responsiveness, Public Service, Public Complaints